ADAPTASI MUSIK PUCATN DAYAK BARAI DALAM PERAYAAN LITURGI GEREJA KATOLIK - Siong; Barnabas Bang (Aggiornamento, 2022)
Pucatn music is music that is used in traditional rituals of the Dayak Barai tribe but is starting to be abandoned. In addition, Pucatn Music has never been used in liturgical celebrations of the Catholic Church. Based on this background, this study aims to explore the meaning of pale music, which has long been neglected, and introduce it into the liturgy of the Catholic Church. Through a qualitative study using a literature review approach, interviews, and phenomenological descriptions, the researchers found that Pucatn music is sacred music for the Barai Dayak tribe. Pucatn music has meaning for the life of the Dayak Barai people and various tones in the music. Second, pale music can be used in liturgical music because it meets the liturgical criteria, namely the compatibility of notes with inculturated liturgical music. Pale music can be used to accompany spiritual songs and can lead people to experience God's salvation.